Irregular elliptic boundary-value problems and Hörmander spaces - Anop, A. V.; Kasirenko, T. M.; Murach, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We study nonregular elliptic problems with boundary conditions of higher orders and prove that these problems are Fredholm on appropriate pairs of the inner-product H¨ormander spaces that form a two-sided refined Sobolev scale. We prove a theorem on the regularity of generalized solutions to the problems in these spaces.